A review of TMJ-related papers published in the British Journal of Oral and Maxillofacial Surgery in 2011 and 2012. Issue 3 (March 2015) - Tahim, A.S.; Goodson, A.M.C.; Payne, K.F.B.; Brennan, P.A.
Abstract This review summarises the articles relating to the temporomandibular joint (TMJ) that were published in the British Journal of Oral and Maxillofacial Surgery (BJOMS) between January 2011 and December 2012. In total 24 papers were published. Of these, 16 (67%) were full-length articles, which included prospective, retrospective, and laboratory-based studies as well as reviews. The remaining 8 papers were short communications, technical notes, and letters to the editor, which report on, amongst other things, unusual cases, rare complications, and novel surgical techniques.